The capacity of local governments to build flood resilience in informal settlements: a social networks approach - Bouwer, Roy (Department of Environmental and Geographical Science, 2017)
As greenhouse gas emissions drive anthropogenic climate change, flooding and flood related risk are likely to increase in frequency and intensity. The burden of these risks are expected to be concentrated in urban areas, particularly affecting highly vulnerable informal settlements. Adapting to these risks will largely fall under the responsibility of local governments. However local governments, in particular those in developing countries, often lack the capacity to implement effective adaptation strategies for long-term resilience. Drawing on social network analysis this research examines the role of social ties and social capital in facilitating knowledge sharing to improve the capacities of local governments to deal with flood-related risks. Using the case studies of Nelson Mandela Bay Metropolitan Municipality and Mossel Bay Local Municipality in South Africa, this research found that patterns of social interactions in the two local governments were largely a result of the size of structures of governance. The larger Nelson Mandela Bay Metropolitan Municipality network consisted of poorly connected sub-groups with poor knowledge dispersal. This led to poor adaptive and inclusive governance because poor levels of collaboration and social learning inhibited effective flood management. The smaller Mossel Bay Local Municipality network consisted of a bonded network with high knowledge transfers. These characteristics contributed to improved adaptive and inclusive governance because strong collaboration enabled informed and flexible flood management. The poor collaboration in NMBMM is likely to negatively affect the municipality's capacity to build resilience for informal settlements by negatively affecting coping, adaptive and transformative capacity. The strong collaboration in MBLM can foster coping and adaptive capacities, but may be hampering the transformative capacity of the municipality. Thus social networks have a considerable role to play in the governance of flooding, thereby influencing the ability of the two local governments to build resilience in informal settlements.